Pengaruh Sistem Aplikasi Keuangan Tingkat Instansi, Kompetensi Sumber Daya Manusia Aparatur, Dan Sistem Pengendalian Intern Pemerintah Terhadap Kualitas Laporan Keuangan Pemerintah - Armay Adelia M B; Christina Dwi Astuti (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to obtain empirical evidence of the influence of SAKTI, SDMA Competency, and SPIP on the Quality of Government Financial Reports. The research was carried out using quantitative methods where the population was Commitment Making Officer (PPK) staff at the Secretariat General (Setjen) of the DPR RI.The PPK staff at the Secretariat General of the DPR RI totals 31 people. This research was carried out by distributing questionnaires via Google Form. The data analysis method uses multiple linear regression. The research results show that the SAKTI, SDMA Competency, and SPIP have a positive effect on the Quality of Government Financial Reports.